Clinical-functional characteristics of children with asthma and obstructive sleep apnea overlap associated with attention deficit hyperactivity disorder: A cross-sectional study - Nguyen-Ngoc-Quynh, Le; Nguyen-Thi-Thanh, Mai; Nguyen-Thi-Phuong, Mai; Le-Quynh, Chi; Le-Thi-Minh, Huong; Duong-Quy, Sy (Frontiers in Neurology, 2023)
Background: Asthma and obstructive sleep apnea (OSA) are common chronic respiratory disorders in children. The relationship between asthma and OSA is bidirectional; these conditions share multiple epidemiological risk factors. Untreated OSA may cause attention deficit hyperactivity disorder (ADHD) symptoms. This study aims to assess the prevalence of ADHD in asthmatic children with OSA and the link between asthma control and lung function of children with asthma and OSA. Methods: A total of 96 children aged 6- 15 years diagnosed with asthma, according to Global Initiative for Asthma (GINA) 2020, were enrolled in this study. All primary data were collected, including age, gender, body mass index, Vanderbilt ADHD Diagnostic Parent Rating Scale, asthma control status, lung function and exhaled nitric oxide, were collected. In addition, home respiratory polygraphy was used to identify OSA in study subjects. Results: 96 patients (8.4 ± 2.4 years) were included in the present study. OSA was identified in 60.4% of asthmatic children with a mean apnea-hypopnea index (AHI) of 3.5 ± 3.0 event/h. The inattentive ADHD subtype was significantly higher in OSA asthmatic group than in the non-OSA asthmatic (34.5% vs 7.9%, p< 0.05). OSA (AHI >1 event/hour) was associated with a higher probability for the presence of ADHD (OR: 2.14; 95% CI: 1.678- 2.474; p < 0.05). A significantly higher risk of OSA was found among children with poorly controlled asthma (83.0% vs. 17.0%, p < 0.001) than among children with well-controlled asthma. Logistic regression analysis showed that allergic rhinitis (OR: 8.217 (95% CI: 3.216- 20.996); p < 0.05) increased the odds of having OSA in subjects with asthma. Conclusion: The prevalence of OSA is increased among poorly controlled asthma. Without treatment, OSA may cause ADHD in children. Therefore, early diagnosis of OSA in asthmatic patients will lead to the appropriate asthma control strategy.